(untitled) (Educação e Pesquisa, 2004)
This article reports on the experiences of the Human Rights in Schools Project in the creation and conduction of a teacher education course aiming at the dissemination of the ideals and values of human rights, democracy and citizenship as guiding principles for each and every school practice, and not just for pedagogical discourses. It must be said that such objective constitutes a great challenge, given the historical features of the Brazilian school and of the Brazilian society at large. Against the backdrop of that challenge, the text summarizes the principles, activities, and reflections resulting from the most significant experiences of the first three years of work of this project in schools belonging to the state and municipal networks in the cities of São Paulo and Osasco. Among other things, this article presents the different forms assumed by the above-mentioned course given the difficulty in shaping activities capable of turning school's everyday practices into an object of reflection for those directly involved in the act of educating, as well as for the school institution as a whole. It also points out important features engendered by this teacher continuing education proposal in its search for answers to the challenges currently faced by the Brazilian school in fulfilling its public role.